Basic Dimensions and Community Welfare in the Boti Tribe in the Island of Timor - Kamilaus Konstanse Oki (Universitas Negeri Malang, 2024)
The Boti tribe is the most unique indigenous traditional tribe on the island of Timor and even in the world. In the economic field, the Boti tribe fulfills economic needs independently through farming and refuses all kinds of government assistance, refuses technological production or modernization and formal education for the younger generation. However, the people of the Boti tribe feel very prosperous with their economic and socio-cultural life. The analytical tool used in this research is SmartPLS. The results show that the basic dimensions formed by the dimensions of satisfaction, meaning in life and security needs determine the very prosperous and happy society in fulfilling basic needs and other needs without dependence on the government and other parties